Linking epigenetic mechanisms of T cell dysfunction with pathophysiology of type 1 diabetes mellitus - Jabri, Abdullah; Elsalti, Abdulrahman; Alsharif, Mohamed; Alsharif, Raghad; Abbad, Tasnim; Sibai, Dania; Taftafa, Bader; Mhannayeh, Abdulaziz; Khan, Mohammad Imran; Yaqinuddin, Ahmed (Frontiers in Immunology, 2025)
β-cell destruction by autoreactive T cells is a hey hallmark of type 1 diabetes mellitus (T1D). Epigenetic mechanisms—including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNAs—play critical roles in regulating T-cell development, activation, and tolerance. Disruption of these processes contributes to immune imbalance and the onset of T1D. This review summarizes current insights into how epigenetic regulation shapes T-cell function and highlights emerging evidence linking these changes to environmental influences such as gut microbiota, diet, and viral infections. Exploring the interaction between genetic susceptibility and environmental triggers through an epigenetic framework not only advances our understanding of T1D pathogenesis but also provides opportunities for biomarker discovery and the development of targeted epigenetic therapies. With further research, these advances hold promise for improving precision medicine strategies in T1D.